GE_GERICHTE C/4825/2017 vom 19. September 2017 - GE Cour de justice (2017)
ACTE DE DÉFAUT DE BIENS ; PÉREMPTION ; OBLIGATION D'ENTRETIEN ; AVANCE(EN GÉNÉRAL) ; MAINLEVÉE PROVISOIRE | LP.82; LP.149a; LARPA.4;